Analysis of factors affecting fear and mental health awareness of coronavirus disease infection - Nursalam, Nursalam; Elsi Dwi Hapsari; Setiawan Setiawan; Ni Luh Putu Inca Buntari Agustini; Diah Priyantini; Khatijah Lim Lim Abdullah (Jurnal Ners, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) is a global health challenge that persists in causing both health emergencies and mental health crises around the world. This study aimed to analyze the factors contributing to COVID-19 infection and their impact on mental health crises on Java Island. Methods: A cross-sectional study was conducted between June and July 2020 on Java Island, Indonesia, involving 1,218 respondents selected through convenience sampling. The independent variables included demographic, individual internal, and psychological factors, while the dependent variable was mental health crisis occurrence. Data were collected through demographic information, knowledge and attitude questionnaires, depression anxiety stress scores, the brief-COPE inventory, as well as surveys addressing encountered problems and mental health emergencies. The collected data underwent analysis using chi-square and multivariate logistic regression. Results: Significance was observed in the relationship between demographic, individual internal, and psychological factors, and their impact on mental health crises (p < 0.05). Following adjustment with logistic regression, psychological factors exhibited a more pronounced relationship, with the highest association observed in stress levels (p = 0.000, 95% CI: 1.064-2.131). Conclusions: Individual stress levels emerged as the foremost contributing factor to mental health crises. Psychological elements, encompassing anxiety levels, stress, coping mechanisms, and encountered challenges, played substantial roles in disrupting psychological well-being and mental health.